Cultural Criminology – Research on the Presentation of Crime in the Media - Pavićević, Olivera (Zbornik Instituta za kriminološka i sociološka istraživanja, 2009)
The purpose of this paper is to present theoretical and research analyses dealing with the media-crime relation, which is a part of cultural criminology. Strong social changes developing in the global society are visible in the relationship of the society toward crime, and in the media image of crime. Although disagreeing concerning the cause and effects of this relation, theoreticians almost unanimously agree with the conclusion that the scope and manner in which crime is presented in mass media is, to a large degree, intensified in comparison to previous decades. Considering the flow and direction of trends of the media presentation of crime through history, the paper gives a review of changes, which most significantly characterise the new position of crime as a phenomenon in society and the media.